Anxiety and Bodily Pain in Older Women Participants in a Physical Education Program. A Multiple Moderated Mediation Analysis. - Chiva-Bartoll, Óscar; Morente-Oria, Honorato Fernando; González-Fernández, Francisco Tomás; Ruiz-Montero, Pedro Jesús (MDPI, 2020)
Background: Bodily pain is normally associated with the consequences of ageing, whereas anxiety shows a high prevalence in elderly people, decreasing the health-related quality of life (HRQoL). Pain coping strategies are used to reduce the consequences of pain, specifically in older people. This study analyzed if the passive and active pain coping strategies were significant moderators in the link between anxiety and bodily pain with a physical component as a mediator. (2) Methods: This cross-sectional study consisted of older women between 60 and 90 years old from small villages with under 5000 inhabitants, of whom 53.8% of the total were participants of a physical education program. Participants of the present study completed all sociodemographic (living alone/accompanied, marital and educational status, number of illnesses, and level of physical activity (PA)) and clinical (anxiety, HRQoL, and pain coping strategies) questionnaires. Anxiety was assessed by the Hospitality Anxiety and Depression Scale (HAD), passive and active strategies by the Vanderbilt Pain Management Inventory (VPMI), and bodily pain and the physical component by the SF-36 questionnaire. (3) Results: The physical component positively predicted bodily pain (p < 0.001) and passive strategies significantly moderated the effect of anxiety on the physical component (p = 0.034). (4) Conclusions: These outcomes help to understand the link between anxiety and bodily pain in older women and the moderation of pain coping strategies in this relationship. In addition, the physical component should be considered when physical education programs aimed at the reduction of bodily pain through the management of anxiety are designed.
Keywords: Mujeres; Ansiedad; Dolor; Educación física; Anxiety; Body Pain; Older Woman; Physical Education